2021
DOI: 10.3390/ani11030716
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermented Rapeseed Meal on the Gastrointestinal Microbiota and Immune Status of Rabbit (Oryctolagus cuniculus)

Abstract: The present study was conducted to determine the effect of the use of varying amounts of fermented rapeseed meal in diets for rabbits on the immune status and microbiota of segments of the GIT. Forty 35 day old rabbits used in the experiment were assigned to four groups: the control group (group C) were fed a standard diet and the experimental received 4%, 8% or 12% fermented rapeseed meal (included in place of standard soybean meal). Class A, G and M immunoglobulins were determined in the blood plasma. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
0
18
1
1
Order By: Relevance
“…An opposite trend was reported by other authors [ 33 , 36 ]. Beshara et al [ 36 ] reported a decrease of total protein, globulin, and WBC in treated groups with probiotics; likewise, Wlazło et al [ 33 ], who studied the effect of fermented rapeseed meal in rabbit diets on immune status, determining the class A, G, and M immunoglobulins in blood plasma, observed a lower level of class G immunoglobulins in the treated group than the control and a decrease of the IgG values as the level of fermented rapeseed meal increased. The same author also observed a correlation between the IgG values and the numbers of microorganisms in the GIT.…”
Section: Effects Of Probiotics On Rabbitscontrasting
confidence: 80%
See 2 more Smart Citations
“…An opposite trend was reported by other authors [ 33 , 36 ]. Beshara et al [ 36 ] reported a decrease of total protein, globulin, and WBC in treated groups with probiotics; likewise, Wlazło et al [ 33 ], who studied the effect of fermented rapeseed meal in rabbit diets on immune status, determining the class A, G, and M immunoglobulins in blood plasma, observed a lower level of class G immunoglobulins in the treated group than the control and a decrease of the IgG values as the level of fermented rapeseed meal increased. The same author also observed a correlation between the IgG values and the numbers of microorganisms in the GIT.…”
Section: Effects Of Probiotics On Rabbitscontrasting
confidence: 80%
“…All the research studies that evaluate GIT microbiota found modification in microorganisms’ populations of GIT in relation to probiotic addition. Wlazło et al [ 33 ] tested the effects of the administration of a fermented rapeseed meal with Bacillus subtilis as the probiotic (strain 87Y from the collection of InventionBio Ltd., Bydgoszcz, Poland) in 35-day-old New Zealand White × Popielno White rabbits for 85 days. The authors enumerate few microbial species in the duodenum, small intestine, caecum, and colon sections.…”
Section: Effects Of Probiotics On Rabbitsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in rabbits, the addition of fermented rapeseed meal contributed to the elongation of the cecum and large intestine, as well as lowering the pH value of the animals’ muscles while increasing their collagen content [ 13 ]. According to Wlazło et al [ 14 ], an 8% or 12% inclusion of fermented rapeseed meal in rabbit diets resulted in a decrease in the concentration of anaerobic bacteria and Escherichia coli in the intestinal contents. Moreover, the addition of fermented rapeseed meals also influences a decrease in the total number of C. perfringens while increasing the number of mesophilic bacteria compared to conventionally fed groups in mink [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, its use is significantly limited by its high fibre content and the presence of anti-nutritional compounds, including glucosinolates, tannins, phytates, and many others [ 1 ]. A new approach which solves the problem of the limited use of RSM is its fermentation [ 2 , 3 ]. In the fermentation process rapeseed protein is hydrolysed by microorganisms, and anti-nutritional substances are inactivated and eliminated.…”
Section: Introductionmentioning
confidence: 99%